Baltų substratas rytų slavų kalbose - Laučiūtė, Jūratė Sofija (Baltistica, 2005)
THE BALTIC SUBSTRATUM IN THE LANGUAGES OF THE EASTERN SLAVSAlthough many archeological and onomastic publications demonstrate the existence of a Baltic substratum over a rather large section of the territory of the Eastern and Western Slavs, some Slavic studies scholars still ignore the influence exerted by this substratum in the evolution of the vocabulary, phonetics and other linguistic aspects of Slavic dialects. One group of linguists adheres to the principle that in elucidating the causes of changes taking place in a language, one must give priority to the patterns of internal language development. Others identify the lexical substratum with marginal (borderland) borrowings. But a drawback to the notion of substratum influence is the extremely large number of common features exclusive to the Baits and the Slavs, such that loanwords are ignored, especially the older loanwords of substratum origin. Scholars find somewhat more substratum Balticisms in the Polish and Belarusian dialects (especially in the Polesje region), but in northwest Russia, where there is a great abundance of hydronyms of Baltic origin, conspicuously few appellative Balticisms are reported.This article not only draws attention to this paradox, but also attempts to determine in which layers of the Russian vocabulary certain still unidentified loanwords from the Baltic languages are concealed.On the basis of the „Atlas substratnoy i zaimstvovannoy leksiki russkich govorov Severo-Zapada“ (Saint Petersburg, 2003), compiled by S. A. Myznikov, it is established that a large portion of the substratum Baltic lexical legacy in northwest Russian dialects is to be found among borrowings from the Finnic languages, e.g.: гумежи ‘field’, галага ‘frost’, xaрм(а) ‘frost’, марьюха ‘female capercaillie (European woodland grouse)’ and other words whose Baltic pedigree is established by S. A. Myznikov. In the Atlas certain Balticisms which might have entered the Russian dialects without the mediation of the Finnic languages are noted: кукорки ‘top section of the back, nape of the neck’, кука ‘a wooden mallet used to stun fish under the ice’, нерет/нерота/нарот ‘a net for catching fish’ and others.The atlas also contains other words which S. Myznikov considers borrowings from the Finnic languages, but which are more likely substratum Balticisms, e.g.: палы‘chaff (of grain), flax husks’ (cf. Lith. pelai ‘grain or hay husks, chaff = Latvian, pelus), керда ‘event; time or instance’ (cf. OPr. kērdan acc. sg. ‘once upon a time’ and Lith. kartas) etc.For lexicologists studying the history and origin of Russian vocabulary it suffices to establish the direct source of the borrowing, without delving into the older origin of the loan word. For this reason Russian Slavic studies scholars would consider most of the words mentioned here Finnicisms, and justifiably so. This does not satisfy Baltic studies scholars, however. It is important for investigators of the language which provided the loanwords to establish not only which neighbouring languages directly borrowed such words, but also the further fate of these „nomadic” words. It is data of exactly this kind which can elucidate the earliest history of the Baltic tribes and their languages about which we can find nothing in the annals of written history.
Keywords: baltų-slavų